Outpatient utilization of psychopharmaceuticals in the city of Zagreb 2001-2006 - Štimac Grbić, Danijela (Array, 2009)
A comprehensive insight into drug utilization as an economic and primarily a public health issue can only be acquired in the context of overall health state of the respective population. The objectives of the study were: 1) to determine the real outpatient utilization of psychopharmaceuticals in Zagreb, 2) to determine the psychopharmaceutical prescribing quality during the study period; and 3) to propose appropriate interventions in Zagreb on the basis of the results obtained. Data on drug utilization were obtained from all Zagreb pharmacies. The number of defined daily doses (DDD) and number of DDD per 1000 inhabitants per day (DDD/1000/day) were calculated from the number of particular drug packages. The Drug Utilization 90% (DU90%) method was used as a criterion of prescribing quality